Translating Nanoparticle-Based Drug Delivery Systems for Natural Products into Clinical Practice: A Pharmacokinetic Perspective - Candra Dwipayana Hamdin; Zaskia Rizky Maulana; Silhiyatun Mayada; Lalu Rifqi Azami (Lombok Medical Journal, 2026)
Secondary metabolites derived from natural products, such as alkaloids,flavonoids, and polyphenols, have promising pharmacological activities, but their clinical use in humans is often restricted by poor solubility, limited gastrointestinal absorption, rapid metabolism, and low systemic bioavailability. Nanoparticle- and formulation-based delivery systems have been developed to address these pharmacokinetic limitations and improvethe therapeutic feasibility of natural product-derived compounds. This literature review discusses the pharmacokinetic enhancement of selected secondary metabolites using nanosuspensions, polymeric nanoparticles, lipid-polymer hybrid nanoparticles, micelles, nanosponges, phytosome-based systems, and nano-sized water-soluble formulations, with emphasis on their potential relevance for human clinical translation. The reviewed studies show improvements in AUC, Cmax, Tmax, half-life, bioavailability, systemic exposure, and tissue distribution compared with conventional formulations. In addition to preclinical evidence, human pharmacokinetic studies on quercetin phytosome, berberine phytosome, and nano-sized curcumin formulation suggest that formulation strategies may improve systemic exposure in humans. These findings support the potential role of nanoparticle and formulation-based delivery systems as translational tools for improving the clinical utility of natural product-derived secondary metabolites. Nevertheless, further studies in patient populations are required to confirm clinical efficacy, long-term safety, and therapeutic relevance.